THE RELATIONSHIP BETWEEN SCREEN TIME AND EMOTIONAL QUOTIENT IN MEDICAL STUDENTS - Justinus Putranto Agung Nugroho; Yanti Ivana Suryanto; Lucas Nando Nugraha; Anggitya Bayu Prakoso (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Background The use of gadgets, especially smartphones, is common among college students. The duration of smartphone usage in a day can be seen through the screen time records. High screen time records indicate high smartphone usage. Excessive use of smartphones has the potential to disrupt social interaction. Emotional Quotient (EQ) is very important in supporting social interaction. Emotional Quotient is a person's ability to express his feelings appropriately and effectively. Objectives This research was conducted to know the relationship between screen time duration and EQ in college students. Methods This research is an analytic observational study with a cross-sectional approach. Respondents in this study were students who met the inclusion and exclusion criteria. They were recruited using the consecutive sampling method. The duration of the screen time is obtained from the default smartphone application. Emotional Quotient was measured with the Trait Emotional Intelligence Questionnaire-Short Form (TEIQue-SF) questionnaire. Results There were 90 respondents (male = 27 people; female = 63 people) with an average age of 19.4 + 0.69 years. Spearman's test showed a relationship between screen time duration and EQ (p<0.01; r=-0.97). Conclusions This study concludes that the duration of screen time is related to EQ, the higher the duration of screen time, the lower the EQ. Therefore, to prevent EQ deterioration, it is important to limit screen time.